2016
DOI: 10.15436/2381-0793.16.1173
|View full text |Cite
|
Sign up to set email alerts
|

Does Glyphosate Acting as a Glycine Analogue Contribute To ALS?

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease involving several protein mutations in glycine-rich regions with limited treatment options. 90-95% of all cases are non-familial with epidemiological studies showing a significant increased risk in glyphosate-exposed workers. In this paper, we propose that glyphosate, the active ingredient in Roundup®, plays a role in ALS, mainly through mistakenly substituting for glycine during protein synthesis, disruption of mineral homeostasis as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 241 publications
0
13
0
1
Order By: Relevance
“…Fast food and a poor diet cause Cancer, Diabetes, Lupus, and many other diseases. This lesson plan will prove the undisputable links between all disease and a common Western diet [24][25][26]. Cancer and many diseases are also caused by other factors in the environment such as genetically modified foods (GMO's), flu shots, child and adult vaccines, prescription drugs, and over-the-counter drugs.…”
Section: Lesson Plan Fast Food and Cancer Linkmentioning
confidence: 99%
“…Fast food and a poor diet cause Cancer, Diabetes, Lupus, and many other diseases. This lesson plan will prove the undisputable links between all disease and a common Western diet [24][25][26]. Cancer and many diseases are also caused by other factors in the environment such as genetically modified foods (GMO's), flu shots, child and adult vaccines, prescription drugs, and over-the-counter drugs.…”
Section: Lesson Plan Fast Food and Cancer Linkmentioning
confidence: 99%
“…Three recent reviews of glyphosate have centred on the idea that glyphosate, acting as an amino acid analogue of glycine, may become incorporated into proteins in place of glycine through a coding error during protein synthesis [48][49][50]. The first study by Samsel and Seneff showed how disruption of multiple proteins in the body with highly conserved glycines could easily explain the correlations seen in the Swanson et al paper [48].…”
Section: 1mentioning
confidence: 99%
“…The first study by Samsel and Seneff showed how disruption of multiple proteins in the body with highly conserved glycines could easily explain the correlations seen in the Swanson et al paper [48]. The study by Seneff et al [49] focused specifically on ALS, and showed that a large number of proteins implicated in ALS have multiple glycine dependencies. The follow-on study by Samsel and Seneff [50] linked glyphosate to multiple autoimmune diseases via molecular mimicry due to resistance to proteolysis of glyphosate-contaminated foreign proteins.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Most ALS experts think these brain afflictions have multiple causes, including genetics, epigenetics[ 4 , 5 ], poor diet, lack of exercise, stress, and a variety of environmental agents, including pathogens[ 6 ], pesticides, for example, pentachlorobenzene, and other chemicals, such as PCBs and formaldehyde[ 7 ]. A recent New England study found pesticides, solvents, or heavy metals, increased the risk of ALS[ 8 ], and Seneff et al[ 9 ] propose that glyphosate (Roundup) causes a number of mechanistic abnormalities associated with ALS, including protein misfolding, and elevated levels of glutamate[ 10 ]. Surprisingly, even silver nanoparticles 100 nm in diameter, commonly used in personal, commercial, and industrial products can, when in aerosol form, be absorbed by the nasal mucosa and travel to the brain where they elicit a microglial, potentially inflammatory, response[ 11 ].…”
Section: Introductionmentioning
confidence: 99%